The Federal Reserve Act and Federal Reserve Policies - Harris, S. E. (Quarterly Journal of Economics, 1931)
I. Introduction, 371. — II. Origins of the Act, 373. — III. Nature of the System, 376. — Eligibility, 378. — Interpretation of eligibility provisions by the Board, 379. — Goodness versus eligibility, 381. — The problem of controlling the use of reserve bank credit, 383. — IV. The position of control, 386. — Open market operations, 387. — Control and the magnitude of member bank indebtedness, 393. — Rediscount rates, 394: — Rate structure in Great Britain and the United States and the significance of the buying rate, 396. — An ineffective discount policy, 399. — Direct methods, 399. — V. Conclusion, 406.